(untitled) (Journal of Universal Science Research, 2023)
Anticorrosive materials are substances or coatings designed to protect metal surfaces from corrosion. These materials play a crucial role in preventing the degradation and deterioration of structures and equipment in various industries. They form a protective barrier that impedes or slows down the electrochemical reactions responsible for corrosion. Coatings and paints are widely used as anticorrosive materials. They create a physical barrier between the metal surface and the surrounding environment, preventing corrosive agents from reaching the metal. Different types of coatings, such as epoxy, polyurethane, and fluoropolymer-based coatings, offer excellent corrosion resistance and durability. They can be applied using methods like spraying, brushing, or dipping.